SPACE-BASED TELEMETRY AND RANGE-SAFETY STUDY TEST RESULTS AND FUTURE OPERATIONAL SYSTEM GOALS - Whiteman, Don (International Foundation for Telemetering, 2003)
International Telemetering Conference Proceedings / October 20-23, 2003 / Riviera Hotel and Convention Center, Las Vegas, Nevada === The use of remote ground stations for telemetry data-relay in space launch applications is costly and limits the geographic locations for launches of future Reusable Launch Vehicle (RLV) systems. The National Aeronautics and Space Administration Space-based Telemetry and Range-Safety (STARS) Study is investigating the use of satellite data relay systems as a replacement or supplement for ground-based tracking and relay stations. Phase-1 of STARS includes flight testing that evaluates satellite data-relay feasibility, defines satellite system performance limitations, and generates requirements for the development of future satellite telemetry data relay systems. STARS Phase-1 ground-test results and goals for the Phase-2 system development and flight-testing are also presented.